A Ming Confucian's World Selections from Miscellaneous Records from the Bean Garden - Rong, Lu (University of Washington Press, 2022)
A forgotten century marks the years between the Ming dynasty's (1368-1644) turbulent founding and its sixteenth-century age of exploration and economic transformation. In this period of social stability, retired scholar-official Lu Rong chronicled his observations of Chinese society in Miscellaneous Records from the Bean Garden (Shuyuan zaji). Openly expressing his admirations and frustrations, Lu provides a window into the quotidian that sets Bean Garden apart from other works of the biji genre of "informal notes." Mark Halperin organizes a translated selection of Lu's records to create a panorama of Ming life. A man of unusual curiosity, Lu describes multiple social classes, ethnicities, and locales in his accounts of political intrigues, farming techniques, religious practices, etiquette, crime, and family life. Centuries after their composition, Lu's words continue to provide a richly textured portrait of China on the cusp of the early modern era. The open access publication of this book was made possible by a grant from the James P. Geiss and Margaret Y. Hsu Foundation.